In Vivo Bioassay of Recombinant Human Growth Hormone Synthesized in B. mori Pupae. (18th March 2010) - Lan, Hanglian; Nie, Zuoming; Liu, Yue; Lv, Zhengbing; Liu, Yingshuo; Quan, Yanping; Chen, Jianqing; Zhen, Qingliang; Chen, Qin; Wang, Dan; Sheng, Qing; Yu, Wei; et al.
Abstract : The human growth hormone (hGH) has been expressed in prokaryotic expression system with low bioactivity previously. Then the effective B. mori baculovirus system was employed to express hGH identical to mature hGH successfully in larvae, but the expression level was still limited. In this work, the hGH was expressed in B. mori pupae by baculovirus system. Quantification of recombinant hGH protein (BmrhGH) showed that the expression of BmrhGH reached the level of approximately 890 μ g/mL pupae supernatant solution, which was five times more than the level using larvae. Furthermore, Animals were gavaged with BmrhGH at the dose of 4.5 mg/rat.day, and the body weight gain (BWG) of treated group had a significant difference (P < .01 ) compared with the control group. The other two parameters of liver weight and epiphyseal width were also found to be different between the two groups (P < .05 ). The results suggested that BmrhGH might be used as a protein drug by oral administration.